Sources of Discomfort in Persons with Dementia: Scale and Initial Results - Jiska Cohen-Mansfield; Khin Thein; Marcia S. Marx; Maha Dakheel-Ali; Barbara Jensen (Behavioural Neurology)
The Sources of Discomfort Scale (SODS) assesses discomfort manifestations based on source of discomfort, thus making it both distinct from and complementary to pain assessments for persons with dementia. Sources were categorized as pertaining to physical discomfort, to body position, and to environmental sources. Body position sources of discomfort were related to poor functional status and to pain. The SODS scores were not related to cognitive functioning, and sources of discomfort other than those pertaining to body position were not correlated with pain. This paper demonstrates a direct and enhanced method to detect the manifestations of discomfort separately from pain indicators in a population with advanced dementia. The determination of the source of discomfort has direct implications for intervention.